Ultrasonographic changes in the liver tumors as indicators of adequate tumor coverage with electric field for effective electrochemotherapy - Boc, Nina (Radiology and oncology (Ljubljana), 2018)
The aim of the study was to characterize ultrasonographic (US) findings during and after electrochemotherapy of liver tumors to determine the actual ablation zone and to verify the coverage of the treated tumor with a sufficiently strong electric field for effective electrochemotherapy. Patients and methods. US findings from two representative patients that describe immediate and delayed tumor changes after electrochemotherapy of colorectal liver metastases are presented. Results. The US findings were interrelated with magnetic resonance imaging (MRI). Electrochemotherapy-treated tumors were exposed to electric pulses based on computational treatment planning. The US findings indicate immediate appearance of hyperechogenic microbubbles along the electrode tracks. Within minutes, the tumors became evenly hyperechogenic, and simultaneously, an oedematous rim was formed presenting as a hypoechogenic formation which persisted for several hours after treatment. The US findings overlapped with computed electric field distribution in the treated tissue, indicating adequate coverage of tumors with sufficiently strong electric field, which may predict an effective treatment outcome. Conclusions. US provides a tool for assessment of appropriate electrode insertion for intraoperative electrochemotherapy of liver tumors and assessment of the appropriate coverage of a tumor with a sufficiently strong electric field and can serve as predictor of the response of tumors.
Keywords: elektrokemoterapija; jetra; načrt zdravljenja; rak (medicina); ultrazvok